Quantifying the Effects of Prior Acetyl-Salicylic Acid on Sepsis-Related Deaths: An Individual Patient Data Meta-Analysis Using Propensity Matching*. Issue 11 (November 2017) - Trauer, James; Muhi, Stephen; McBryde, Emma S.; Al Harbi, Shmeylan A.; Arabi, Yaseen M.; Boyle, Andrew J.; Cartin-Ceba, Rodrigo; Chen, Wei; Chen, Yung-Tai; Falcone, Marco; Gajic, Ognjen; Godsell, Jack; et al.
Abstract : Objective: The primary objective was to conduct a meta-analysis on published observational cohort data describing the association between acetyl-salicylic acid (aspirin) use prior to the onset of sepsis and mortality in hospitalized patients. Study Selection: Studies that reported mortality in patients on aspirin with sepsis with a comparison group of patients with sepsis not on prior aspirin therapy were included. Data Sources: Fifteen studies described hospital-based cohorts ( n = 17, 065), whereas one was a large insurance-based database ( n = 683, 421). Individual-level patient data were incorporated from all selected studies. Data Extraction: Propensity analyses with 1:1 propensity score matching at the study level were performed, using the most consistently available covariates judged to be associated with aspirin. Meta-analyses were performed to estimate the pooled average treatment effect of aspirin on sepsis-related mortality. Data Synthesis: Use of aspirin was associated with a 7% (95% CI, 2–12%; p = 0.005) reduction in the risk of death as shown by meta-analysis with considerable statistical heterogeneity ( I 2 = 61.6%). Conclusions: These results are consistent with effects ranging from a 2% to 12% reduction in mortality risk in patients taking aspirin prior to sepsis onset. This association anticipates results of definitive studies of the use of low-dose aspirin as a strategy for reduction of deaths in patients with sepsis. Abstract : Supplemental Digital Content is available in the text.